Effects of sea urchin feces on behaviors, digestion ability, growth, and resistance of the sea cucumber Apostichopus japonicus - Yu, Yushi; Qiao, Yihai; Ding, Peng; Tian, Ruihuan; Sun, Jiangnan; Hu, Fangyuan; Wu, Guo; Chang, Yaqing; Zhao, Chong (Frontiers in Marine Science, 2022)
Improving the aquaculture production efficiency by appropriate diets is an essential approach to meeting the increasing market demand for sea cucumbers. The feces of sea urchins, which contains various enzymes and microorganisms, is a potentially cost-effective food for sea cucumbers. A five-week laboratory simulation is conducted to investigate behaviors, digestion ability, growth and resistance ability of the sea cucumber Apostichopus japonicus fed with fecal diet at water temperatures of 15 °C and 5 °C. In the present study, A. japonicus fed with fecal diet shows an obvious preference to fecal diet rather than prepared feed at water temperatures of both 15 °C and 5 °C, which suggests that the feces is an applicable diet for A. japonicus. Furthermore, small A. japonicus fed with feces (group F) shows significant advantages in intestinal community richness, community diversity and intestine protease activity to A. japonicus fed with prepared feed (group S) at 15 °C. These results indicate that the fecal diet provides benefits to digestion ability of small A. japonicus at 15 °C. Weight gaining rate is significantly higher in the A. japonicus fed with feces than that in A. japonicus that were fed with feed or not fed with food (group C), which suggests that the direct improvement of the production efficiency at 15 °C. The advantages in intestinal bacteria, protease activity, and growth are consistently found in group F compared with group S at 5 °C. In addition, the composition of intestinal bacteria indicates that sea cucumbers may inherit the intestinal bacteria of sea urchins through fecal consumption. This suggests that the fecal diet enhances the digestion ability and enzyme activity at low water temperature and thus improves the growth of sea cucumbers. Furthermore, sea cucumbers fed with sea urchin feces have the highest survival rate among the three groups in exposure to an acute salinity decrease at both 5 and 15 °C, indicating a better resistance to low salinity. In conclusion, the present study suggests that sea urchin feces have a great potential for the application in improving the production efficiency of sea cucumber aquaculture.